2014
DOI: 10.1007/s13277-014-2985-7
|View full text |Cite
|
Sign up to set email alerts
|

Timosaponin AIII mediates caspase activation and induces apoptosis through JNK1/2 pathway in human promyelocytic leukemia cells

Abstract: Timosaponin AIII (TAIII) is a steroidal saponin isolated from Anemarrhena asphodeloides that has been shown to inhibit cell growth and induce apoptosis in cancer. However, the effect of TAIII on acute myeloid leukemia (AML) remains unclear. Here, the molecular mechanism by which TAIII-induced apoptosis affects human AML cells was investigated. The results showed that TAIII significantly inhibited cell proliferation of four AML cell lines (MV4-11, U937, THP-1, and HL-60). Furthermore, TAIII induced apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Flavokawain B induces apoptosis in a variety of cancer cells . We therefore determined whether FKB also induces apoptosis of TCa cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavokawain B induces apoptosis in a variety of cancer cells . We therefore determined whether FKB also induces apoptosis of TCa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Flavokawain B induces apoptosis in a variety of cancer cells. [19][20][21] We therefore determined whether FKB also induces apoptosis of TCa cells. Increases in apoptosis were observed in three cell lines in early (annexin V+/propidium iodide [PI]−) and late (annexin V+/PI+) stages with FKB at 24 h ( Fig.…”
Section: Flavokawain B Inhibits Growth Of Tca Cellsmentioning
confidence: 99%
“…Cantharidin and CA are the selective inhibitors of serine/threonine phosphatase 1 and 2A, and represent an important aspect of cell apoptosis . Apoptosis is a procedure of programmed cell death involving caspases occurring in cells as inactive proenzymes . Previous studies have shown that cantharidin induced apoptosis through blocks the cell cycle, and this effect is mediated by cell cycle arrest at the G2/M phase .…”
Section: Discussionmentioning
confidence: 99%
“…32 Thus, SK-Hep-1 cells are very critical cell lines applied in investigation, and the involving caspases occurring in cells as inactive proenzymes. 35,36 Previous studies have shown that cantharidin induced apoptosis through blocks the cell cycle, and this effect is mediated by cell cycle arrest at the G2/M phase. 17,37 CA is a phosphatase inhibitor and thus induces cytochrome c release and elevated activation of caspase-3 in the pancreatic beta cell line HIT.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Anemarrhenae (Zhimu in Chinese), a wellknown traditional Chinese medicinal herb, which is officially listed in the Chinese Pharmacopoeia, has been effectively used for febrile diseases in oriental clinical practices. Timosaponin A-III (TAIII), a steroidal saponin isolated from the rhizomes of Anemarrhena asphodeloides (AA), has been credited with a wide spectrum of bioactivities, including improving learning and memory (16), inhibiting inflammation (17), suppressing allergic reaction (18), controlling hyperglycemic (19,20), activating autophagy (21) and inducing cancer cells apoptosis (22)(23)(24). However, the ability of TAIII to reverse MDR has not been reported.…”
Section: Introductionmentioning
confidence: 99%